A "H2O donating/methanol accepting" platform for preparation of highly selective Nafion-based proton exchange membranes1. Issue 36 (28th September 2015) - Feng, Kai; Tang, Beibei; Wu, Peiyi
<x xml:space="preserve">Abstract</x> A "H2O donating/methanol accepting" approach is exploited to alleviate critical drawbacks of Nafion and thereby fabricate highly selective PEMs.